Millennium Development Goals and the Republic of Maldives - Srivastava, Gouri (THE PRIMARY TEACHER, 2009)
The present millennium is marked by several countries world over including Maldives, drawing road map to achieve the Millennium Development Goals (MDG). In the realm of education, primary and secondary data portray that the Republic is close to achieving the MDG. Educational indicators such as high literacy rate and enrolment of all children in schools at the primary level are indicative of this. However, in-depth field works undertaken in different schools in Male and few islands in 2007, reveal that in terms of quality in education the Republic faces certain challenges that need to be addressed for achieving quality education. A detailed account of issues concerning quality education in the Republic is highlighted in the present paper